Potensi Physalis Angulata (Ciplukan) sebagai Manajemen Kelainan pada Kulit - kurniasih, wuriandaru; Yuniaswan, Anggun (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Physalis angulata is a plant from the Solanacea family that has been used as a traditional treatment for various diseases in various countries including Indonesia. Various phytochemicals have been isolated from Physalis angulata which contain carbohydrates, fats, minerals and vitamins and secondary metabolites, namely physalin, withangulatin, saponins, tannins, flavonoids and others. This plant has various pharmacological activities such as anti-inflammatory, immunomodulating, antiproliferation, antioxidant, antibacterial, and others that support extracts of leaves, fruit, stems, and roots with different phytochemicals. Since time immemorial Physalis angulata is also a traditional medicine for a variety of skin disorders, such as wounds, ulcer and inflammation. Currently, research on P. angulata for skin disorders has been developed such as adjuvant therapy for scleroderma, accelerated wound healing and irritant contact dermatitis. Given the vast pharmacological activity of Physalis angulata, this plant is highly considered a therapeutic modality for a variety of skin diseases. For this reason, research on safety and types of extracts is still needed to determine the active ingredients that are useful for each disease.